2014
DOI: 10.1177/014556131409300702
|View full text |Cite
|
Sign up to set email alerts
|

Reinnervation of Facial Muscles with Only a Cross-Facial Nerve Graft in a 25-Year-Old Patient with Congenital Facial Palsy

Abstract: The standard method for managing chronic facial palsy is the two-stage free-muscle flap. We report a case involving a 25-year-old patient who had facial palsy from her birth. Twelve months after the first stage of a cross-facial nerve graft, we found that the voluntary movements of her facial muscles had returned. Within the following 12 months, she gained complete recovery of her movements on the affected side, as confirmed by electromyography studies. This case demonstrates that neurotization of facial muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…CFNGs can also be used to motor a free muscle transfer in the case of chronic paralysis patients or in conjunction with a hypoglossal transfer. Seyed-Forootan et al reported using the sural nerve as a CFNG in a patient with complete peripheral facial nerve palsy [ 52 ]. Before the surgery, the electromyography (EMG) showed no muscle movement on the left side of the face.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CFNGs can also be used to motor a free muscle transfer in the case of chronic paralysis patients or in conjunction with a hypoglossal transfer. Seyed-Forootan et al reported using the sural nerve as a CFNG in a patient with complete peripheral facial nerve palsy [ 52 ]. Before the surgery, the electromyography (EMG) showed no muscle movement on the left side of the face.…”
Section: Resultsmentioning
confidence: 99%
“…Before the surgery, the electromyography (EMG) showed no muscle movement on the left side of the face. The patient gained the ability to move her left facial muscles after 12 months post-surgery, and, after 24 months, the EMG showed complete recovery without any subsequent free muscle transfer [ 52 ]. The obvious disadvantage of CNFG is the prolonged denervation of the affected facial muscles while regeneration of the contralateral axons occurs, leading to irreversible muscle atrophy unless the CNFG procedure is performed during the first 6 months from the nerve injury [ 4 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%